2011
DOI: 10.1371/journal.pone.0027132
|View full text |Cite
|
Sign up to set email alerts
|

Infant Pupil Diameter Changes in Response to Others' Positive and Negative Emotions

Abstract: It has been suggested that infants resonate emotionally to others' positive and negative affect displays, and that these responses become stronger towards emotions with negative valence around the age of 12-months. In this study we measured 6- and 12-month-old infants' changes in pupil diameter when presented with the image and sound of peers experiencing happiness, distress and an emotionally neutral state. For all participants the perception of another's distress triggered larger pupil diameters. Perceiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 75 publications
8
135
1
2
Order By: Relevance
“…While these emotional expressions may represent just the use of adequate social interaction means, they may also indicate empathic-like responses. When the cues for social interaction were reduced, Geangu et al (2011b) found that both 6-and 12-month-old infants show an increased emotional arousal, as indexed by increased pupil dilation, for another's joy but for shorter duration than for perceived distress. The increase in arousal to positive emotions compared to neutral states has a longer delay for 6-than for 12-month-old infants.…”
Section: Positive Empathymentioning
confidence: 97%
“…While these emotional expressions may represent just the use of adequate social interaction means, they may also indicate empathic-like responses. When the cues for social interaction were reduced, Geangu et al (2011b) found that both 6-and 12-month-old infants show an increased emotional arousal, as indexed by increased pupil dilation, for another's joy but for shorter duration than for perceived distress. The increase in arousal to positive emotions compared to neutral states has a longer delay for 6-than for 12-month-old infants.…”
Section: Positive Empathymentioning
confidence: 97%
“…At as early as six months, some infants manifest directed other-oriented behaviours to peers expressing distress, while rarely becoming distressed themselves [82]. Infants have been shown to more robustly express empathy around eight months [83,84]. Preverbal infants show rudimentary empathic concern toward others, as indexed by their evaluation of characters' interactions.…”
Section: Empathy and Prosocial Behaviour (A) What Is Prosocial Behavimentioning
confidence: 99%
“…These sympathetic reactions, in turn, are often induced by empathy or affect sharing (i.e., experiencing emotions similar to the ones of the other), suggesting that empathy relates to prosocial behavior (e.g., Eisenberg, Spinrad, & Sadovsky, 2006;Hoffman, 2000;Young, Fox, & Zahn-Waxler, 1999). Early instances of empathic reactions can already be observed in the first year of life (e.g., Hay, Nash, & Pedersen, 1981;Roth-Hanania, Davidov, & Zahn-Waxler, 2011), whereby these reactions are especially strong toward negative emotions (e.g., Geangu, Hauf, Bhardwaj, & Bentz, 2011). Theoretically, it has been proposed that a direct perception-action coupling is the basis of this phenomenon (Preston & de Waal, 2002) and that there is thus a biological basis for the capacity for empathy (see also Hastings, Zahn-Waxler, & McShane, 2006).…”
Section: Comfortingmentioning
confidence: 99%